2016
DOI: 10.1016/j.euprot.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The identification of FERM domain protein in serum infected with Plasmodium berghei

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(22 reference statements)
1
0
0
Order By: Relevance
“…It usually occurs in the initiation of metastasis in cancer progression. Loss of E-cadherin and gain of N-cadherin are considered to be fundamental events in EMT 21,22. In the present study, we found that columbamine inhibited N-Cadherin expression, and promoted E-cadherin expression, thus inhibiting EMT in colon cancer cells.…”
Section: Discussionsupporting
confidence: 63%
“…It usually occurs in the initiation of metastasis in cancer progression. Loss of E-cadherin and gain of N-cadherin are considered to be fundamental events in EMT 21,22. In the present study, we found that columbamine inhibited N-Cadherin expression, and promoted E-cadherin expression, thus inhibiting EMT in colon cancer cells.…”
Section: Discussionsupporting
confidence: 63%